2020
DOI: 10.3389/fonc.2020.00815
|View full text |Cite
|
Sign up to set email alerts
|

Hyperviscosity Syndrome in Paraprotein Secreting Conditions Including Waldenstrom Macroglobulinemia

Abstract: Hyperviscosity syndrome is a serious complication associated with high levels of paraproteins in patients with hematological malignancies. Therapeutic advances in disease control may reduce the incidence of hyperviscosity syndrome; however, management of acute cases requires an understanding of key symptoms and prompt treatment to mitigate serious consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
0
19
1
Order By: Relevance
“…There is a high degree of clinical overlap between BNS and other WM complications, and even experienced clinicians struggle to differentiate them. As an example, we discussed a patient (case 2) who presented with blurred vision and a headache, both of which could have been caused by hyperviscosity, a condition associated with WM ( 16 ). Notably, in one patient (case 1), the median and ulnar nerve impairments were the most prominent symptoms at BNS onset, indicating the presence of mononeuropathy or peripheral neuropathies that can be seen in WM.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high degree of clinical overlap between BNS and other WM complications, and even experienced clinicians struggle to differentiate them. As an example, we discussed a patient (case 2) who presented with blurred vision and a headache, both of which could have been caused by hyperviscosity, a condition associated with WM ( 16 ). Notably, in one patient (case 1), the median and ulnar nerve impairments were the most prominent symptoms at BNS onset, indicating the presence of mononeuropathy or peripheral neuropathies that can be seen in WM.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in blood viscosity leads to the development of hyperviscosity syndrome. Of note, hyperviscosity syndrome is developed in different hematological disorders, including multiple myeloma, sickle cell anemia, Waldenstorm macroglobulinemia, polycythemia, and leukemia (21,22). Normal BV is usually between 1.4 and 1.8 centipoise (cp), and symptoms of hyperviscosity syndrome develop when blood viscosity exceeds 4.0 cp (23).…”
Section: Blood Viscosity and Hyperviscosity Syndromementioning
confidence: 99%
“…Normal BV is usually between 1.4 and 1.8 centipoise (cp), and symptoms of hyperviscosity syndrome develop when blood viscosity exceeds 4.0 cp (23). Patients with hyperviscosity syndrome are presented with diving symptoms due to impairment of blood flow, including headache, confusion, visual disturbances, vertigo, and thrombotic events with or without mucosal hemorrhage (21,22). Sloop and colleagues found that inflammation and hypergammaglobulinemia together with the fostering of erythrocyte aggregation in sepsis could be the potential mechanisms of increasing blood viscosity in different infectious diseases (24).…”
Section: Blood Viscosity and Hyperviscosity Syndromementioning
confidence: 99%
“…Higher IgM levels (>4000 mg/dl) and/or serum viscosity >4 centipoise (normal value-1.5) are usually associated with these symptoms. 20 A classic fundoscopic finding in WM associated with hyperviscosity is the presence of dilated, segmented, and tortuous retinal veins. Hemorrhages, exudates, and papilledema can also be seen.…”
Section: Clinical Manifestationsmentioning
confidence: 99%